Relationship between individual and composite FMS™ scores with the anthropometric and physical characteristics of elite touch (rugby) players - Thorpe, C.; Dobbin, N.; Twist, C.; Callaghan, M. (Journal of Science in Sport and Exercise, 2024)
Purpose To describe and compare the movement patterns, anthropometric and physical characteristics of male and female Touch players; and examine the relationships between Functional Movement Screening (FMS™) scores and the anthropometric and physical characteristics.